2019
DOI: 10.5539/jas.v11n16p1
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automated Phenotyping of Soybean Seedlings and Its Relation With Physiological Seed Quality

Abstract: The development of procedures enabling agility and effectiveness to the analyses of seed vigor are great advances for the seed research field. The aim of this paper was to evaluate the efficiency of the Seedling Analysis System (SAPL®) to seedling phenotyping and determining the physiological potential of soybean seeds, in comparison with the information provided by traditional vigor tests recommended for this species. The characterizing of physiological potential of the seed lots was carried out based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Thus, evaluation of seedling shoot length does not appear to be sensitive to detect vigor differences in chickpea seed lots. In a study regarding semiautomated phenotyping, the authors found that shoot length obtained through computerized image analysis did not exhibit sufficient sensitivity for vigor evaluation in soybean seeds (Silva et al, 2019b). *, ns = significant and not significant by the F test at 5% probability; F = F value calculated; CV = coefficient of variation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, evaluation of seedling shoot length does not appear to be sensitive to detect vigor differences in chickpea seed lots. In a study regarding semiautomated phenotyping, the authors found that shoot length obtained through computerized image analysis did not exhibit sufficient sensitivity for vigor evaluation in soybean seeds (Silva et al, 2019b). *, ns = significant and not significant by the F test at 5% probability; F = F value calculated; CV = coefficient of variation.…”
Section: Resultsmentioning
confidence: 99%